Motivating Retail Sales Personnel Customer Orientations: An Empirical Study - Bhattacharya, Debasis; Ray, Subrata (Indian Journal of Marketing, 2011)
Although customer orientation is a core element of the marketing concept, so it is very crucial in the concept of relationship marketing. However, no widely accepted conceptualization of the construct still exists. In sales organizations, the fulfilment of the customer needs and wishes by customer-contact employees can be seen as crucial for gaining a high degree of customer orientation. Customer Orientation of Retail Sales Personnel requires greater expenditure of efforts by the sales personnel to interact with a heterogeneous group of customers. The sales personnel should be motivated continuously to practice customer orientation for satisfying customers. In this research, the researchers try to draw from the job characteristics model (JCM) to argue that retail sales personnel motivation to engage in customer orientation is impacted by the extent to which they experience their work as meaningful and affective evaluations of two aspects of their working environment: their identification with the values of their organization and their satisfaction with the pay they receive. Research results were derived from the responses of 120 sales personnel of a large retail outlet chain operating in the national market in India. The findings of the results revealed that customer orientation is influenced by experienced meaningfulness, job stress and other job related facets. Managerial implications and directions for future research and limitations of the study are also discussed.